If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(w + -7) + -8w = -36 Reorder the terms: 6(-7 + w) + -8w = -36 (-7 * 6 + w * 6) + -8w = -36 (-42 + 6w) + -8w = -36 Combine like terms: 6w + -8w = -2w -42 + -2w = -36 Solving -42 + -2w = -36 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + -2w = -36 + 42 Combine like terms: -42 + 42 = 0 0 + -2w = -36 + 42 -2w = -36 + 42 Combine like terms: -36 + 42 = 6 -2w = 6 Divide each side by '-2'. w = -3 Simplifying w = -3
| 10h-7h=18 | | 13h+7h=20 | | s-7500=18000 | | 7x+25+3x=16-2x-3 | | 8m+2=9m+4 | | 4v+3-3(-5v-1)=5(v-2) | | 2t-t=7 | | -2(-2)-7y=-2 | | 18d-15d=9 | | 4v+3-3(-5v-1)=5(v+2) | | x^3+8x^2+14x+4=0 | | 2(5x+3)=-36-4x | | 9.12*9.12= | | 10y=2y+72 | | 9.11*9.11= | | 9.15*9.15= | | -31+3a=4(a-7) | | x+3(2x+5)=6 | | -8(1+3x)-6x=172 | | n-8=19-11 | | 9.21*9.21= | | n^2-12n+13=-7 | | 3(r-5)+2(r-4)=-2(r-1)+8(r+2) | | 8(7r+5)=320 | | 6x-5=109 | | 8(7r+5)=330 | | e^4x=e^2x+6 | | 2/3=2-2 | | 2a+14-13=-7 | | a^2+8a+6=-9 | | b-33=145 | | 4+2(2)+3x=11 |